Effect of Different Carbon Sources on In vitro Shoot Regeneration of Solanum nigrum (Linn) - An Important Antiulcer Medicinal Plant - C.V. Naidu*, T.M. Sridhar and (Journal of Phytology, 2011)
An efficient in vitro protocol for mass propagation of Solanum nigrum was developed.Ã‚Â In the present study, the effect of various carbon sources, sucrose, glucose, fructose, and maltose was investigated on in vitro shoot regeneration using nodal explants. The frequency, growth and multiplication rate were highly influenced by the type and concentration of carbon sources used.Ã‚Â The highest number of shoots (24.0Ã‚Â±0.28) were obtained on MS medium supplemented with 4% fructose, but maximum shoot length (11.0Ã‚Â±0.28 cm) was observed on MS medium supplemented with 4% sucrose. The least number of shoots obtained on MS medium supplemented with 1% glucose (3.5Ã‚Â±0.50), with a shoot length of (3.4Ã‚Â±0.34 cm). Among the different carbon sources used in the present study, fructose at 4% proved to be better choice for multiple shoot regeneration followed by sucrose, maltose and glucose, from nodal explants of Solanum nigrum.